The role of plasma cortisol in dementia, epilepsy, and multiple sclerosis: A Mendelian randomization study - Li, Haiqi; Chen, Kaili; Yang, Le; Wang, Qiaoli; Zhang, Jiao; He, Jinting (Frontiers in Endocrinology, 2023)
Background: Many clinical studies have shown a correlation between plasma cortisol and neurological disorders. This study explored the causal relationship between plasma cortisol and dementia, epilepsy and multiple sclerosis based on Mendelian randomization (MR) method. Methods: Data were taken from the summary statistics of a genome-wide association study, FinnGen consortium and United Kingdom Biobank. Dementia, epilepsy, and multiple sclerosis were used as outcomes, and genetic variants associated with plasma cortisol were used as instrumental variables. The main analysis was performed using the inverse variance weighted method, and the results were assessed according to the odds ratio (OR) and 95% confidence interval. Heterogeneity tests, pleiotropy tests, and leave-one-out method were conducted to evaluate the stability and accuracy of the results. Results: In two-sample MR analysis, the inverse variance weighted method showed that plasma cortisol was associated with Alzheimer’s disease (AD) [odds ratio (95% confidence interval) = 0.99 (0.98-1.00), P = 0.025], vascular dementia (VaD) [odds ratio (95% confidence interval) = 2.02 (1.00-4.05), P = 0.049)], Parkinson’s disease with dementia (PDD) [odds ratio (95% confidence interval) = 0.24 (0.07-0.82), P = 0.023] and epilepsy [odds ratio (95% confidence interval) = 2.00 (1.03-3.91), P = 0.042]. There were no statistically significant associations between plasma cortisol and dementia with Lewy bodies (DLB), frontotemporal dementia (FTD) and multiple sclerosis. Conclusion: This study demonstrates that plasma cortisol increase the incidence rates of epilepsy and VaD and decrease the incidence rates of AD and PDD. Monitoring plasma cortisol concentrations in clinical practice can help prevent diseases, such as AD, PDD, VaD and epilepsy.